New data of Ye Yen Sun granite complex in Phan Si Pan uplift - Dung, Pham Thi; Hoa, Tran Trong; Anh, Tran Tuan; Hieu, Tran Van; Ly, Vu Hoang; Ching-Ying, Lan; Usuki, Tadashi (Vietnam Journal of Earth Sciences, 2012)
Cenozoic granitic YeYenSun complex is distributed mainly in the northwest PhanSiPan uplift region, comprising Sa Pa-Binh Lu, Tung Qua Lin-Si Lo Lau, Nam Xe-Sin Suoi Ho, and Chung Leng Ho-Po Ho sections. The complex is composed of biotite granite, biotite-amphibole granite of small to medium grained size, light colored and porphyre dacite, showing almost no deformation. The magmas are relatively enriched in aluminium, potassium, sodium oxides, large ionic lithophile elements (Rb, Ba, K) and light rare earth elements (LREE), but depleted in high field strength element contents (Nb, Ta, Zr, Hf), having Lacroix index >0.6. These geochemical characteristics indicat that Cenozoic granite in the PhanSiPan uplift region corresponds to high K calcalkaline granite, result of mixture between mantle - crust. The zircon LA-ICP-MS U-Pb age of the light colored biotite granite at Silver falls is 32.94-30.7 Ma suggesting that the YeYenSun granite is Oligocene as it has been identified.